2021
DOI: 10.3758/s13414-021-02369-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of time structure on prediction motion in visual and auditory modalities

Abstract: Usually people can estimate the correct position of a moving object even when it temporarily moves behind an occlusion. Studies have been performed on this type of occluded motion with prediction motion (PM) tasks in the laboratory. Previous publications have emphasized that people could use mental imagery or apply an oculomotor system to estimate the arrival of a moving stimulus at the target place. Nevertheless, these two ways cannot account for the performance difference under a different set of conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 50 publications
4
7
0
Order By: Relevance
“…The results were consistent with those of position PM tasks: From the view of CE results, participants tended to overestimate CTEs when T = 0.5 and T = 1.0 (Qin et al, 2022). Participants tended to underestimate CTEs when T = 1.5 (Li et al, 2015).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The results were consistent with those of position PM tasks: From the view of CE results, participants tended to overestimate CTEs when T = 0.5 and T = 1.0 (Qin et al, 2022). Participants tended to underestimate CTEs when T = 1.5 (Li et al, 2015).…”
Section: Resultssupporting
confidence: 85%
“…The VE results indicated that participants performed more stably at equal time structure condition than at unequal time structure conditions. In addition, the results of RMSE demonstrated that the participants’ performance was significantly higher at equal time structure condition than unequal time structure conditions (Chang & Jazayeri, 2018; Qin et al, 2022).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Modality is the term used to describe the behavioral or physiological sources of information. The principal behavioral modalities are auditory, body language, tactile, and facial expressions [ 20 , 41 ].…”
Section: Artificial Intelligence In Pain Detectionmentioning
confidence: 99%